2022
DOI: 10.1002/mds.28977
|View full text |Cite
|
Sign up to set email alerts
|

Gait‐Related Metabolic Covariance Networks at Rest in Parkinson's Disease

Abstract: Background Gait impairments are characteristic motor manifestations and significant predictors of poor quality of life in Parkinson's disease (PD). Neuroimaging biomarkers for gait impairments in PD could facilitate effective interventions to improve these symptoms and are highly warranted. Objective The aim of this study was to identify neural networks of discrete gait impairments in PD. Methods Fifty‐five participants with early‐stage PD and 20 age‐matched healthy volunteers underwent quantitative gait asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…At baseline, PD-FoG-converters showed higher global and parietal local efficiency and clustering coefficient relative to PD-FoG cases and healthy controls, suggesting an increased functional communication in the parietal network and globally in the brain in PD-FoG-converters. These findings are in line with recent evidence supporting the presence of a cholinergic up-regulation in specific gait control networks (including the parietal lobe) as a compensatory mechanism to counteract aberrant dopaminergic function in PD 35 , 36 . The pattern of increased parietal clustering coefficient might also represent an attempt to compensate for the incremental structural alteration of posterior cortical areas in PD-FoG-converters 34 .…”
Section: Discussionsupporting
confidence: 91%
“…At baseline, PD-FoG-converters showed higher global and parietal local efficiency and clustering coefficient relative to PD-FoG cases and healthy controls, suggesting an increased functional communication in the parietal network and globally in the brain in PD-FoG-converters. These findings are in line with recent evidence supporting the presence of a cholinergic up-regulation in specific gait control networks (including the parietal lobe) as a compensatory mechanism to counteract aberrant dopaminergic function in PD 35 , 36 . The pattern of increased parietal clustering coefficient might also represent an attempt to compensate for the incremental structural alteration of posterior cortical areas in PD-FoG-converters 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a metabolic temporal variability gait covariance network in PD was recently reported to correlate with variability of step and swing time. This network was characterised by predominantly decreased brain glucose metabolism (associated with increased step and swing time variability) in the caudate nucleus, hippocampus, and red nucleus, which all receive cholinergic input from cell groups within the basal forebrain and the pedunculopontine nucleus (PPN) [11]. Research has shown that the number of acetylcholinesterase + neurons in the PPN is reduced in PD fallers relative to those patients without balance deficits and a history of falls [12].…”
Section: Introductionmentioning
confidence: 99%